MnO2 Supported Pt Nanoparticels with High Electrocatalytic Activity for Oxygen Reduction Reaction. Issue 1 (10th December 2013) - Wang, X.; Yang, Z.; Zhang, Y.; Jing, L.; Zhao, Y.; Yan, Y.; Sun, K.
Abstract We report the hydrothermal synthesis of manganese dioxide (MnO2) and its application as platinum nanoparticles (PtNPs) support for oxygen reduction reaction (ORR). The prepared MnO2 samples with different hydrothermal reaction time were systematically investigated by X‐ray diffraction (XRD) and scanning electronic microscopy (SEM), conforming that the crystalline structure of samples was transferred from γ phase to β phase, and the morphology was changed from microspheres to nanorods, respectively. The ORR activity of the samples was evaluated by rotating ring‐disk electrode (RRDE) method and the optimized sample was further utilized as PtNPs support to form a new nanocomposite used as ORR catalyst. We show that the 1 wt.%Pt@MnO2 has a promising performance toward the electrochemical catalytical reduction of oxygen, which an overall quasi 4‐electron transfer in ORR, as well as a limiting reduction current of 0.71 mA was achieved. In comparison with commercialized Pt@C and other Pt‐based catalysts, the MnO2 supported PtNP exhibited remarkable mass activity (per unit mass of Pt), as high as 7.07 mA μg–1, in alkaline solution. We demonstrate that the hydrothermal synthesized MnO2 may offer useful applications as reliable, cost‐effective and morphology controllable support for PtNP as efficient ORR catalysts.